Growth inhibition of head and neck squamous cell carcinoma cells by sgRNA targeting the cyclin D1 mRNA based on TRUE gene silencing. - Satoshi Iizuka; Nobuhiko Oridate; Masayuki Nashimoto; Satoshi Fukuda; Masato Tamura (PLoS ONE)
Head and neck squamous cell carcinoma (HNSCC) exhibits increased expression of cyclin D1 (CCND1). Previous studies have shown a correlation between poor prognosis of HNSCC and cyclin D1 overexpression. tRNase ZL-utilizing efficacious gene silencing (TRUE gene silencing) is one of the RNA-mediated gene expression control technologies that have therapeutic potential. This technology is based on a unique enzymatic property of mammalian tRNase ZL, which is that it can cleave any target RNA at any desired site by recognizing a pre-tRNA-like complex formed between the target RNA and an artificial small guide RNA (sgRNA). In this study, we designed several sgRNAs targeting human cyclin D1 mRNA to examine growth inhibition of HNSCC cells. Transfection of certain sgRNAs decreased levels of cyclin D1 mRNA and protein in HSC-2 and HSC-3 cells, and also inhibited their proliferation. The combination of these sgRNAs and cisplatin showed more than additive inhibition of cancer cell growth. These findings demonstrate that TRUE gene silencing of cyclin D1 leads to inhibition of the growth of HNSCC cells and suggest that these sgRNAs alone or combined with cisplatin may be a useful new therapy for HNSCCs.